Optimization of Medium‐Deep Borehole Thermal Energy Storage Systems. Issue 1 (10th November 2015) - Schulte, Daniel Otto; Rühaak, Wolfram; Oladyshkin, Sergey; Welsch, Bastian; Sass, Ingo
Abstract: Arrays of medium‐deep borehole heat exchangers are characterized by their slow thermal response and large storage capacity. They represent suitable thermal energy storage systems for seasonally fluctuating heat sources such as solar energy or district heating grids. However, the economic feasibility of these systems is compromised by high investment costs, especially by the expensive drilling of the boreholes. This study presents an approach for the simulation and optimization of borehole thermal energy storage systems. To exemplify the concept, a software tool is used to optimize the number and length of borehole heat exchangers with regard to a specific annual heat demand. The tool successfully determines the ideal size of the thermal energy storage. Furthermore, the prediction of the system's performance also indicates that borehole thermal energy storage systems only operate efficiently in large‐scale applications. With the presented tool, many aspects of borehole thermal energy storage systems can be simulated and optimized. Abstract : Things are heating up! An array of borehole heat exchangers tapped into the subsurface rock can serve as a thermal storage volume. However, high investment costs for borehole drilling compromise the economic feasibility. Avoiding oversized systems is imperative. This study presents a versatile software tool for the mathematical optimization of borehole thermal energy‐storage systems and gives an application example for finding the ideal size of a borehole array.